Farming system database - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
The Association for Farming System Research and Extension (AFSRE) is developing a database on networks interested in FSRE. The Association is compiling a computerized database on networks interested in, or carrying information relevant to, any or...